Interrelation Kiai Authorities, Curriculum and Learning Culture in Pesantren Indonesia - Mohammad Muchlis solichin (TARBIYA: Journal of Education in Muslim Society, 2018)
AbstractIn the education system of Pesantren salaf (traditional Islamic boarding school), Kiai is the highest authority in determining the direction and policies of a pesantren. The figure of Kiai in Pesantren has the authority to determine the direction, the purpose of education, and curriculum/learning materials in Pesantren. Kiai has authority in determining the books of certain scholars. Some books are specifically used in Pesantren to provide guidance for students in implementing the learning process in Pesantren.Those books are selected by Kiai to provide guidance for students in implementing the learning process in this Pesantren. This writing seeks to discuss mutual and interrelated relations among kiai’s authorities, curriculum and norms of students in learning. This paper will discuss how Kiai with authority to select and specify the books on the provisions of the students in learning. While such rules directly strengthen and perpetuate the leadership of Kiai in Pesantren. AbstrakDalam sistem pendidikan Pesantren salaf, Kiai adalah otoritas tertinggi dalam menentukan arah kebijakan pesantren. Sosok Kiai di Pesantren, memiliki wewenang untuk menentukan arah, tujuan pendidikan, kurikulum\materi pembelajaran di Pesantren. Kiai memiliki otoritas dalam menentukan kitab-kitab para Ulama tertentu. Beberapa kitab secara khusus digunakan di Pesantren untuk membimbing siswa dalam melaksanakan proses pembelajaran di Pesantren. kitab tersebut dipilih oleh Kiai untuk membimbing siswa dalam melaksanakan proses pembelajaran di Pesantren ini. Tulisan ini berusaha untuk membahas hubungan timbal balik dan saling terkait antara otoritas kiai, kurikulum dan norma-norma siswa dalam pembelajaran. Tulisan ini akan membahas bagaimana Kiai dengan wewenangnya memilih dan menentukan kitab-kitab belajar  siswa. Sementara aturan tersebut langsung memperkuat dan melanggengkan kepemimpinan Kiai di Pesantren.